PERSPEKTIF THOMAS DJAMALUDDIN TERHADAP EKSISTENSI FAJAR ṠADIQ DALAM PENENTUAN AWAL - selfiah febriani; Andi Muhammad Akmal; Hamzah Hasan (Universitas Islam Negeri Alauddin Makassar, 2022)
Syafi'iyah fiqh which concludes that the deadline for Fajr time is until the sun appears. The dawn of adiq is placed in the context of an astronomical dawn called astronomical twilight. Dawn from an Astronomical Point of View, clearly distinguishes the definition of shadiq dawn and kadzib dawn. Fajar adiq is also commonly called the true dawn, namely the light of dawn that comes from sunlight (original), while Fajar kadzib means dawn that comes from sunlight (not original). on the determination of the time for the dawn prayer refers to the hadiths of the apostle regarding prayer times and their indications and that the dawn of kadzib (false dawn) is a light that appears on the eastern horizon, rising upwards, originating from the scattering of sunlight by inter-planetary dust. In astronomical terminology, it is called the zodiacal light. Meanwhile, the dawn of adiq (the true dawn or the real dawn) is a light that appears on the eastern horizon, expanding on the horizon originating from the scattering of sunlight by the earth's atmosphere. Astronomical terminology is called twilight, especially astronomical twilight. This study aims to determine the study of Fajar adiq in Jurisprudence and Astronomy in determining the time of the dawn prayer and to find out the opinion of Thomas Djamaluddin about the existence of Fajar adiq in determining the time of the dawn prayer. This type of research is descriptive qualitative literature (library research). Research that reveals an event that occurred by using scientific mechanisms to answer the actual problem. The approach used by the researcher is the syar'i, scientific and juridical approach. According to the data source, the research data is divided into two data, namely primary data and secondary data.